Effects of Striker Compliance on Dynamic Response and Brain Tissue Strain for Helmeted Ice Hockey Impacts - de Grau Amezcua, Santiago (Université d'Ottawa / University of Ottawa, 2017)
The effect of striking compliance in ice hockey impacts, and its influence on dynamic response and brain tissue strain was investigated in this study. In hockey, players can experience a broad range of striking/surface compliance during a head impact, from the stiff ice surface to highly compliant player collisions. An increase in striking compliance has been shown to extend the duration of an impact that is associated with an increase in risk of sustaining brain injuries. Three striking caps of low, medium, and high compliance were used to impact a helmeted 50th percentile Hybrid III male headform attached to an unbiased neckform. Each level of compliance was used to impact five high risk locations at three different velocities, representative of head impact scenarios in ice hockey. The dependent variables, peak resultant linear accelerations and peak resultant rotational acceleration as well as MPS, were analyzed using a multivariate analysis of variance (MANOVA) to determine if there were significant differences between the three controlled variables. The results demonstrate a significant effect of compliance, over the influence of velocity and acceleration. Conditions of low impact compliance resulted in higher response values compared to impacts of increased compliance. That being said, high compliance conditions remained in the range of concussion risk, even at the lowest velocity. The use of brain tissue modeling, compared to dynamic response alone, demonstrated an elevated risk of brain injury as a result of extended impact durations. Impact compliance in hockey is a factor that has not been considered when designing and testing helmet technology. The results of this study demonstrate that compliance is a determining factor in producing brain injury, and should be incorporated into helmet standard testing to mitigate risk. The results of this study have implications on brain injury risk that extend beyond the impacting scenarios of ice hockey. The results can be extrapolated to any contact sport that includes impacting scenarios against varied impacting compliances such as football and rugby.
Keywords: Biomechanics; Hockey; Concussion; Helmet